The economic returns to field of study and competencies among higher education graduates in Ireland - Elish Kelly; Philip O'Connell; Emer Smyth (The Economic and Social Research Institute (ESRI), 2008)
This paper looks at the economic returns to different fields of study in Ireland in 2004 and also the value placed on various job-related competencies, accumulated on completion of higher education, in the Irish labour market. In examining these issues the paper seeks to control for potential selection influences by ensuring through quantile regression that comparisons are made within sections of the wage distribution where ability differences are likely to be minimal. The impact that education-job mismatch, both education-level and field, has on earnings is also taken into consideration. The results derived indicate that, relative to the base case, there are higher returns to Medicine & Veterinary, Education, Engineering & Architecture, Science and Computers & IT. The quantile regression analysis reveals that the OLS estimates are not particularly affected by unobserved heterogeneity bias. Furthermore, this approach indicates that field specific returns diminish the more able the graduate. Small but significant returns were found for some of the competencies analysed, in particular technical skills.
Keywords: I20; J24; J30; J31; 330; field of study; competencies; returns to education; quantile regression; Ireland; Bildungsniveau; Studienfach; Qualifikation; Einkommen; Irland